2010
DOI: 10.1021/ic902257u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, and Photoluminescence of Homodinuclear Lanthanide 4-(Dibenzylamino)benzoate Complexes

Abstract: Three new binuclear lanthanide complexes of general formula [Ln 2 (L) 6 (H 2 O) 4 ] (Ln = Tb (1), Eu (2), and Gd (3)) supported by the novel aromatic carboxylate ligand 4-(dibenzylamino)benzoic acid (HL) have been synthesized. Complexes 1 and 2 were structurally characterized by single-crystal X-ray diffraction. Both 1 and 2 crystallize in the triclinic space group P 1 , and their molecular structures consist of homodinuclear species that are bridged by two oxygen atoms from two carboxylate ligands via differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 83 publications
(48 reference statements)
9
81
0
Order By: Relevance
“…The design of suitable organic ligands favoring structurespecific self-assembly is one of the keys for the construction of discrete coordination architectures. In fact, besides coordination bonding, some weak intra-or intermolecular intermolecular interactions, such as hydrogen bonding [5,6], p···p stacking [7,8] and C-H···p [9,10] interactions also affect the final structures of the complexes, and they may further link discrete subunits or lowdimensional entities into higher-dimensional supramolecular frameworks [5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…The design of suitable organic ligands favoring structurespecific self-assembly is one of the keys for the construction of discrete coordination architectures. In fact, besides coordination bonding, some weak intra-or intermolecular intermolecular interactions, such as hydrogen bonding [5,6], p···p stacking [7,8] and C-H···p [9,10] interactions also affect the final structures of the complexes, and they may further link discrete subunits or lowdimensional entities into higher-dimensional supramolecular frameworks [5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…3 It was also demonstrated that replacement of the hydrogens of the NH 2 moiety of p-aminobenzoic acid by benzyl groups had a significant influence on the distribution of π-electron density within the ligand system and resulted in the development of a novel solid state photosensitizer for Tb 3+ with an overall quantum yield of 82%. 4 Subsequent investigations from our group also revealed that the presence of electron-releasing or electron-withdrawing groups on position 3 of the 4-benzyloxy benzoic acid ligand has a profound effect on the π-electron density of the ligands and consequently on the photosensitization of the Ln 3+ ions. Specifically, the presence of a methoxy substituent in this position results in a significant improvement in the photoluminescence efficiency of the Tb 3+ -3-methoxy-4-benzyloxy benzoate complex in comparison with that of the 4-benzyloxy benzoate complex (10-33%).…”
Section: Introductionmentioning
confidence: 95%
“…Among the five emission bands, the electric dipole transition 5 D0→ 7 F2 around 616 nm is the strongest. In addition, the ratio of electric dipole transition and magnetic dipole transition ( 5 D0→ 7 F1) of Complexes 1 and 2 are 3.31 and 4.28, respectively, which indicates that the coordination environment of Eu 3+ complexes are not center symmetric [50][51][52][53][54]. The luminescence intensities of electric dipole transition of Complexes 1 and 2 are 0.74 × 10 5 and 1.4 × 10 5 , respectively.…”
Section: Luminescence Of the Europium Complexesmentioning
confidence: 94%